2021
DOI: 10.1111/1467-8489.12426
|View full text |Cite
|
Sign up to set email alerts
|

Trade creation, political sensitivity and product exclusions: the political economy of agriculture protection in China’s FTAs*

Abstract: One of the most significant features in Free Trade Agreement (FTA) is that certain products are excluded from tariff concession. Why do some products get more protection in FTAs?In this paper, using the highly disaggregated product-level data in agricultural sector of China's FTAs, we examined and extended the hypothesis developed by Grossman and Helpman (1995), illustrating the products which are more likely to be excluded in FTAs. Our results suggest that, with the involvement of political costs to incumbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Harada and Nishitateno (2021) examined the impact of preferential tariff reductions under FTAs on the wine trade in China, Japan, and South Korea [20]. Lyu et al (2021) found that China tends to gain economic benefits from large trading partners and non-economic benefits from concessions to smaller trading partners in FTA negotiations [21]. Haq et al (2021) and Shah et al (2022) analyzed the China-Pakistan FTA (CPFTA) in terms of RCA and the advantages and disadvantages brought about by the FTA, and they found that the CPFTA has generally had a positive effect on China-Pakistan trade [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Harada and Nishitateno (2021) examined the impact of preferential tariff reductions under FTAs on the wine trade in China, Japan, and South Korea [20]. Lyu et al (2021) found that China tends to gain economic benefits from large trading partners and non-economic benefits from concessions to smaller trading partners in FTA negotiations [21]. Haq et al (2021) and Shah et al (2022) analyzed the China-Pakistan FTA (CPFTA) in terms of RCA and the advantages and disadvantages brought about by the FTA, and they found that the CPFTA has generally had a positive effect on China-Pakistan trade [22,23].…”
Section: Introductionmentioning
confidence: 99%